Effects of Simulation-Guided Microwave Presintering Process on the Preparation and Final Properties of Pure Ceramic Rings: Lower Sintering Temperature and Higher Mechanical Properties - Xiao Lu; Tong-Tong Zhou; Feng-He Zhao; Xiao-Xiong Wang; Li-Xiang Chen; Yun-Ze Long (Advances in Materials Science and Engineering)
In order to improve the performance and endurance of steel rings used for twisting and winding yarns in the textile industry, a more wear-resistant ceramic version is studied and examined by conducting multiple simulations combined with microwave sintering experiments of the ring preparation process, aiming to reduce manufacturing costs and improve efficiency. The three-dimensional (3D) electromagnetic field simulation software HFSS is used to simulate the electromagnetic field distribution in the microwave sintering cavity and to determine the electromagnetic region with the most uniform electromagnetic field to guide the microwave sintering experiments. The 3Y-TZP ceramic rings are shaped by gel-casting. The effect of presintering on the performance of ceramic rings is investigated by applying conventional sintering and microwave sintering methods. The experimental results show that the simulation-guided microwave sintering process can resolve the deficiency of uneven microwave sintering at low temperatures. Comparing the final sintering temperatures and mechanical properties of the final ceramic-sintered rings obtained by microwave presintering to those obtained by conventional presintering, microwave presintered sample has a final temperature of 1400°C, which is 100°C lower than that of conventional presintering, which is 1500°C; its average grain size of 0.18 μm is dramatically smaller than that of conventional presintering, which is 0.24 μm, with about 80% of the grain sizes present in the range of 0.1-0.2 μm and a relative density of about 99%, as opposed to conventional presintering’s 70% falling between 0.2 and 0.3 μm and relative density of about 98%; the Vickers hardness and fracture toughness for microwave presintered sample reach 1550 kg·f·mm−2 and 9.05 MPa m1/2, respectively, which are both greater than 1431 kg·f·mm−2 and 8.86 MPa m1/2 in the conventional samples.